Analysis of Planning and Budget Consistency on The Quality of Government Agency Performance Accountability Reports in the Simeulue District - Mujahid, Abdullah; darwanis, darwanis; Abdullah, Syukriy (PT FORMOSA CENDEKIA GLOBAL, 2024)
The assessment of the Simeulue Regency Government Agency Performance Accountability System documents for the 2017 - 2022 period still received a sufficient title of